2013
DOI: 10.1186/1743-422x-10-26
|View full text |Cite
|
Sign up to set email alerts
|

Porcine epidemic diarrhea virus E protein causes endoplasmic reticulum stress and up-regulates interleukin-8 expression

Abstract: BackgroundPorcine epidemic diarrhea virus (PEDV) is an important pathogen in swine and is responsible for substantial economic losses. Previous studies suggest that the PEDV E protein plays an important role in the viral assembly process. However, the subcellular localization and other functions of PEDV E protein still require more research.MethodsThe subcellular localization and function of PEDV E protein were investigated by examining its effects on cell growth, cell cycle progression, interleukin-8 (IL-8) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 33 publications
2
81
0
Order By: Relevance
“…When PEDV infects porcine IECs, its entrance is mediated by receptors such as aminopeptidase N protein (Belouzard et al, 2012) or sugars (Deng et al, 2016;Liu et al, 2015) expressed on porcine IECs (Cong et al, 2015;Jung and Saif, 2015). It has been reported that the virus infected epithelium results in barrier dysfunction by downregulation of tight junction proteins (Zhao et al, 2014) and an increase in interleukin (IL)-8 (Xu et al, 2013) and necrotic cell death . However, the mechanism that defends against PEDV infection in porcine IECs is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…When PEDV infects porcine IECs, its entrance is mediated by receptors such as aminopeptidase N protein (Belouzard et al, 2012) or sugars (Deng et al, 2016;Liu et al, 2015) expressed on porcine IECs (Cong et al, 2015;Jung and Saif, 2015). It has been reported that the virus infected epithelium results in barrier dysfunction by downregulation of tight junction proteins (Zhao et al, 2014) and an increase in interleukin (IL)-8 (Xu et al, 2013) and necrotic cell death . However, the mechanism that defends against PEDV infection in porcine IECs is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The cell cycle was measured by using propidium iodide staining as described previously (Xu et al, 2013;Tang et al, 2010). Briefly, approximately 2 Â 10 6 cells of the stable cell lines and control cells were treated with trypsin, washed with phosphate-buffered saline (PBS) for twice, resuspended in 75% ethanol and fixed at 4 8C for 3 days.…”
Section: Cell Cycle Analysis By Flow Cytometrymentioning
confidence: 99%
“…The procedures of Real-time quantitative PCR were described previously (Xu et al, 2013). Briefly, total RNA was extracted from cells using TRIzol agent (Invitrogen, California, USA), and 2 mg each RNA sample was reversetranscribed using First-strand cDNA synthesis kit (Invitrogen, California, USA).…”
Section: Real-time Quantitative Pcr (Qrt-pcr)mentioning
confidence: 99%
“…The M protein is the most abundant virion component and also contains conserved linear B-cell epitopes (Zhang et al, 2012). The E protein is responsible for the assembly of virion, and it causes endoplasmic reticulum stress and interleukin-8 expression up-regulation (Xu et al, 2013a). Accessory genes are dispensable for virus growth in vitro, but they may play an important role in the virus survival in the infected host.…”
Section: Swine Coronavirusesmentioning
confidence: 99%